Maternal and paternal alcohol consumption in the prenatal period and mental health and behavior of their children until adulthood - Mohrová, Zuzana; Csajbók, Zsófia; Kšiňan, Albert; Andrýsková, Lenka; Brennan Kearns, Pavla (European psychiatry, 2025)
Maternal alcohol consumption can adversely affect children's development, but the impact of paternal drinking is less understood. We aimed to investigate whether maternal or paternal alcohol consumption during pregnancy affected children's mental health and behavior. A total of 2,013 parent-child triads from the European Longitudinal Study of Pregnancy and Childhood cohort were used. Data on alcohol consumption was obtained from questionnaires during pregnancy and after the child's birth. Mental health and behavior of children were assessed with Strength and Difficulties Questionnaire (SDQ). The associations were tested using linear regression, adjusting for socio-demographic and psychosocial covariates. Increased maternal alcohol consumption was associated with higher total SDQ scores at ages 7, 11, and 18 years old when the outcomes were reported by mothers, but only at 11 years when reported by children. We did not observe any dose-response relationship, and the effect size did not change during the follow-up. The effects were observed across various domains of SDQ: in the emotional symptoms subscale at age 11, in the conduct problems subscale at ages 7 and 11, and in the hyperactivity/inattention subscale at age 18. Paternal alcohol consumption was not associated with SDQ. Maternal alcohol consumption during pregnancy is associated with long-term effects on children's mental health and behavior, particularly when reported by mothers. No association was found between paternal alcohol consumption, suggesting that the results may stem from biological effects of alcohol or other factors beyond the direct exposure, potentially encompassing broader maternal psychosocial or behavioral characteristics.